2018
DOI: 10.3354/meps12546
|View full text |Cite
|
Sign up to set email alerts
|

Replicated marine protected areas (MPAs) support movement of larger, but not more, European lobsters to neighbouring fished areas

Abstract: The European lobster Homarus gammarus is heavily exploited in the Norwegian fishery, and several management actions have been implemented to protect the species. Three marine protected areas (MPAs) excluding all but hook and line type fishing gear were established along the Skagerrak coast in 2006, effectively banning the trap-based fishery for European lobster. Lobster populations within MPAs and adjacent control areas were studied by capture-markrecapture and recovery methods every year from prior to MPA est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
1
20
1
2
Order By: Relevance
“…This could diminish the ability to detect these population changes altogether. However, while some studies have detected increases in CPUE within MPAs (Nillos Kleiven et al, 2019) and increases in mean size of lobsters within MPAs (Thorbjørnsen et al, 2018), the present study implies that consideration of the increased inhibitory effect of increasing size or density of lobsters should be taken in to account in determining that change.…”
Section: Discussioncontrasting
confidence: 65%
“…This could diminish the ability to detect these population changes altogether. However, while some studies have detected increases in CPUE within MPAs (Nillos Kleiven et al, 2019) and increases in mean size of lobsters within MPAs (Thorbjørnsen et al, 2018), the present study implies that consideration of the increased inhibitory effect of increasing size or density of lobsters should be taken in to account in determining that change.…”
Section: Discussioncontrasting
confidence: 65%
“…In this sense, harvest of large individuals leaving the MPA and temporary use of the MPA by individuals from control areas (resulting in lower mortality risks) may explain part of the size-dependent survival patterns observed in later years at some MPA-Control area pairs. However, we are cautious with this explanation, as observed movements between MPAs and control areas are sparse (15 and 33 individuals leaving and entering MPAs, respectively; Thorbjørnsen et al 2018), and other still unidentified causes may explain the survival increases seen outside our study MPAs.…”
Section: )mentioning
confidence: 82%
“…Indeed, high emigration rates have been documented for Atlantic cod in Flødevigen following increases in individual density several years after protection (Fern andez-Chac on et al 2015), and there are indications (i.e., catch per unit effort estimates) that lobster abundance levels have also increased in the studied MPAs (Moland et al 2013). Recently, Thorbjørnsen et al (2018) reported some spillover of large individuals off MPA boundaries in our study system but also some movement from harvested to protected areas (spill-in), especially in the Vestfold sites due to the proximity and existence of habitat corridors between the local MPA and adjacent control area. In this sense, harvest of large individuals leaving the MPA and temporary use of the MPA by individuals from control areas (resulting in lower mortality risks) may explain part of the size-dependent survival patterns observed in later years at some MPA-Control area pairs.…”
Section: )mentioning
confidence: 96%
See 1 more Smart Citation
“…An increased average body size (13%) of lobster in MPAs relative to controls was evident after 4 years of protection from the annual lobstering season (Moland et al, 2013a), an effect somewhat dampened by introduction of a 25 cm MLS in 2008. Thorbjørnsen et al (2018) presented "before" (2006) and "after" (2014) data on the demography of lobster in the three original MPAs, demonstrating a substantial widening of the size structure in the protected populations compared to the harvested beforestate. By 2014, the average size increase in MPAs was 15% compared to 1% in control areas.…”
Section: Recovery Of Size Structurementioning
confidence: 99%